Study on elements concentrations on seabird feathers by instrumental neutron activation analysis. - Carolina Yume Sawamura Theophilo; Rubens Cesar Lopes Figueira; Fernanda Imperatrice Colabuono; Rosalinda Carmela Montone; Edson Gonçalves Moreira (Brazilian Journal of Radiation Sciences)
Seabirds are very sensitive to environmental changes and due to their large longevity they are also sensitive to cumulative impacts. These birds usually occupy the higher trophic levels. White-chinned petrel (Procellaria aequinoctialis) and black-browed albatross (Thalassarche melanophris) are Procellariiformes, which is a seabird order, composed of 4 families. In the last years, researches are being done and actions are being taken to reduce the mortality of albatrosses and petrels caused by human activities. Due to the great ecological importance of these birds and the developed work with Procellariiformes, this study purpose was to quantify the Br, Cl, Cu, K, Mg, Mn, Na and V elements in white-chinned petrel and black-browed albatross feathers. Bird specimens were killed accidentally by pelagic longline fisheries operating off southern Brazil. Feathers were cleaned with acetone and then milled in a cryogenic mill. Instrumental Neutron Activation Analysis (INAA) was used for quantification of the element concentrations and measurements of induced activities were performed in a High Purity Germanium (HPGe) detector for gamma ray spectrometry. The obtained results on feathers showed that concentrations in these birds are not higher than others studies with the same species and, with exception of Br, there are no significant differences between elements mean concentrations in the two seabirds.